2016
DOI: 10.1097/md.0000000000002975
|View full text |Cite
|
Sign up to set email alerts
|

Graves Disease Is Associated With Endometriosis

Abstract: The aim of this cross-sectional study was to compare the prevalence of thyroid diseases between women with and without endometriosis.We established the endometriosis group according to diagnosis codes, surgery codes, and gonadotropin-releasing hormone agonist codes using the Korean Health Insurance Review and Assessment Service—National Inpatients Sample (HIRA-NIS) from 2009 to 2011. Four controls were randomly matched to each endometriosis case. Thyroid disease cases were selected using the thyroid disease di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…This study showed that there was a relationship between endometriosis and simple non-toxic goitre. A previous study using HIRA-NIS reported that there was no association between endometriosis and simple non-toxic goitre 4 . This result seems to be due to differences in the definition of simple non-toxic goitre.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This study showed that there was a relationship between endometriosis and simple non-toxic goitre. A previous study using HIRA-NIS reported that there was no association between endometriosis and simple non-toxic goitre 4 . This result seems to be due to differences in the definition of simple non-toxic goitre.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies questioned the relationship between specific diseases and endometriosis based on individual experience or from previous studies 24,11 . However, such a method has several disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 5 ] It mainly manifests as the dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia, especially as the endometriosis-associated pain (EAP). [ 6 9 ] It can result in frequent chronic pain and even infertility, if such condition cannot be treated very well. [ 10 13 ] Many factors may lead to this issue, including retrograde menstruation, genetic, environment, and immune factors.…”
Section: Introductionmentioning
confidence: 99%
“…Так, за даними деяких дослідників [78][79][80], естрадіол посилює реакцію тиреотропного гормону на тироліберин. Тироліберин відносять також до стимуляторів секреції пролактину (поряд із пролактоліберином).…”
unclassified